The Relationship Between Gender Self-Stereotyping and Life Satisfaction: The Mediation Role of Relational Self-Esteem and Personal Self-Esteem - Li, Junnan; Liu, Yanfen; Song, Jingjing (Frontiers in Psychology, 2022)
Individuals voluntarily internalize gender stereotypes and present personality characteristics and behaviors that conform to gender role requirements. The aim of the current study was to explore the reasons people internalize gender stereotypes. We conducted surveys with 317 college students in China to examine the relationship between gender self-stereotyping and life satisfaction. We also analyzed the mediating roles of relational self-esteem (RSE) and personal self-esteem (PSE) and the moderation role of gender. The results of path analysis showed that gender self-stereotyping directly affected life satisfaction and indirectly affected life satisfaction through RSE and PSE in a serial pattern; however, the serial mediation model was only significant in the male sample. Higher gender self-stereotyping was associated with male participants’ higher level of RSE and PSE, and further corelated with higher life satisfaction. This study addressed the questions: “What are the benefits of gender self-stereotyping?” and “What are the major barriers to counter-stereotyping?” The results enrich our understanding of these issues, especially relative to the collectivist culture in China, and may be used to create more effective interventions to help people break through the stereotypes.